Estudo de proposta de implantação de ferrovia de carga para acesso a porto marítimo de grande significância: o caso da Nova Ferroeste - Souza, Gabriel Sacillotto Reis [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The Port of Paranaguá is the third biggest national port in terms of total amount of cargoes handled, and, despite of a huge part of these cargoes being solid bulks, they are transported to the port mostly by roadway, less efficient than railway for carrying this kind of cargo. The railway that gets to the port is historic and technically outdated, resulting in logistic bottlenecks to the operation of Rumo Malha Sul, the dealership responsible for the stretch. Given that, Paraná State Government, trying to make its state transportation matrix more efficient, plans to construct a new railway, called New Ferroeste, connecting Dourados city, in the state of Mato Grosso do Sul, to the Port of Paranaguá, having published, in November 2017, a Request for Proposal for the making of the railway feasibility studies. To understand the several knowledge areas involved in the development of an infrastructure project as extensive and important as the New Ferroeste, this final paper analyzed and discussed legal, technical and environmental aspects of the railway modeling process, through technical bibliography survey and monitoring of the studies developed by one of the consortia that attended to the Request for Proposal

O Porto de Paranaguá é o terceiro maior porto nacional em termos de quantidade total de cargas movimentadas, e, apesar de parte expressiva dessa movimentação ser granéis sólidos, essas cargas chegam ou saem do porto majoritariamente pelo modo rodoviário, menos eficiente que o modo ferroviário no transporte desse tipo de carga. A ferrovia que chega ao porto é histórica e tecnicamente ultrapassada, impondo gargalos logísticos à operação da Rumo Malha Sul, concessionária que opera o trecho. Assim, o Governo do Estado do Paraná, visando tornar mais eficiente a matriz de transportes de seu estado, planeja construir uma ferrovia, chamada de Nova Ferroeste, ligando a cidade de Dourados, no Mato Grosso do Sul, ao Porto de Paranaguá, tendo lançado, em novembro de 2017, um Procedimento de Manifestação de Interesse para a realização dos estudos de viabilidade da ferrovia. Para compreender as diversas áreas do conhecimento envolvidas no desenvolvimento de um projeto de infraestrutura tão extenso e importante quanto o da Nova Ferroeste, este trabalho analisou e debateu aspectos jurídicos, técnicos e ambientais da modelagem da ferrovia, por meio de levantamento de literatura técnica e acompanhamento do trabalho realizado por um dos consórcios participantes do Procedimento de Manifestação de Interesse
Study of the proposal for the implementation of a cargo railroad for access to a maritime port of great significance: the case of Nova Ferroeste
Keywords: Ferrovias; Transporte ferroviario; Concessões administrativas; Railroads